Early childhood cognitive stimulation from working and non-working mothers - Sulaiman Samad; Hasnawi Haris; Suardi Suardi (Jurnal Cakrawala Pendidikan, 2023)
This article reports on the results of an in-depth analysis of the intentional daily behavior performed by mothers in facilitating the cognitive development of a child aged under five years old. This study employed a descriptive design. It involved 147 mothers (72 working mothers and 75 non-working mothers) who were selected using the purposive sampling technique (non-probability sampling). Research data were gathered using a questionnaire. The questionnaire contained two major components that evaluated a mother’s presence as the designer of the home environment (two indicators) and cognitive stimulation provided by a mother at home (six indicators). The collected data were analyzed with descriptive statistics making use of the Microsoft Excel 16.10 version application. The results suggest that employment status does not influence a mother’s presence as the designer of the home environment. In other words, both working and non-working mothers have provided the best home environment for their child's cognitive development. However, regarding the fulfillment of the child's cognitive development needs, non-working mothers are able to supply more adequate stimulation than working mothers.